2014
DOI: 10.12659/pjr.889816
|View full text |Cite
|
Sign up to set email alerts
|

Radiological imaging in pediatric rheumatic diseases

Abstract: SummaryRadiological imaging plays a fundamental role in the diagnosis and monitoring of rheumatic diseases. The basic method of imaging is a classic X-ray picture, which for many years has been used as a single method for the recognition and evaluation of the effects of disease management. In today’s modern day treatment of rheumatic diseases, ultrasonography and magnetic resonance are more commonly performed for early detection of inflammatory changes in the region of soft tissue, subchondral bone and bone ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Below, we present radiographic pictures of individual entities belonging to the group of juvenile spondyloarthropathies, according to the ESSG classification ( 27 ) . Subsequently, in the second part of that paper, we will discuss the usefulness of US and MRI in the diagnosis of early inflammatory changes in the course of JSpA.…”
Section: Imaging Of Juvenile Spondyloarthritismentioning
confidence: 99%
“…Below, we present radiographic pictures of individual entities belonging to the group of juvenile spondyloarthropathies, according to the ESSG classification ( 27 ) . Subsequently, in the second part of that paper, we will discuss the usefulness of US and MRI in the diagnosis of early inflammatory changes in the course of JSpA.…”
Section: Imaging Of Juvenile Spondyloarthritismentioning
confidence: 99%
“…Early diagnosis of rheumatic disease in children and adolescents is important because of the increasing possibility of applying an appropriate form of comprehensive treatment, including targeted pharmacotherapy that offers the possibility of permanent remission. This is particularly relevant in children, as delaying treatment of rheumatic disease can lead to growth and developmental disorders and permanent disability [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Juvenile spondyloarthritis has been associated with articular involvement of the lower limbs, but not sternoclavicular involvement. However, the SCJs may be one of the first joints to become involved in juvenile ankylosing spondylitis [13]. A previous case-control study reported 14 patients with juvenile spondyloarthritis accompanied with costosternal pain, six of which had reduced chest expansion [14].…”
Section: Introductionmentioning
confidence: 99%